Pumping System Controlled by Neuro-fuzzy - Mansouri smail; Ouled ali Omar (AIMS Energy, 2019)
The irrigation system in Foggara is adopted by peasants in the Algerian south. Over the years, the water level in the vertebrates has decreased, which has caused the migration of many peasants to their traditional agricultural lands. The studied system aims to strengthen the Foggara with deep wells that rely on large pumps, which are rotated by electric machines of high capacity. To ensure the maintenance of the water level, we control the speed of the DFIM machine and thus control the level of water flow. The controlled type of control is the control of the neuro-fuzzy, because it has many positive properties, for example, not associated with changes related to the electrical properties of the machine, such as resistance, self, etc.